Implementasi Model Sentra untuk Mendukung Perkembangan Sosial-Emosional Anak Usia Dini - Idrus, N Defa Alwiyyah; Rahiem, Maila Dinia Husni (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2026)
Early childhood socio-emotional development is a critical domain that requires optimal stimulation through appropriate pedagogical approaches; one such approach is the center-based learning model implemented at TK Islam Pembangunan. This study aims to examine how the center-based model supports childrens socio-emotional development and to identify enabling and constraining factors in its implementation. Using a descriptive qualitative design, interviews were conducted with one principal, four teachers, and four parents. The findings indicate that the model promotes socio-emotional growth by (1) cultivating empathy, collaboration, and independence; and (2) integrating Qur’anic memorization (tahfidz) and extracurricular activities. Implementation was facilitated by (1) regular teacher training and (2) routine team meetings with collaborative problem-solving. Constraints included (1) limited budgets for learning media and professional development, (2) shortages of trained teaching staff, and (3) irregular cycles of evaluation (observation–reflection–assessment). The study recommends follow-up research employing more diverse samples and larger settings to provide a comprehensive account of the implementation of the center-based learning model.